Strain fatigue life prediction model of 2A70 aluminum alloy in the full life range - ZHANG JunHai; JING GuoXi; LIU Ye; ZHANG WenKai; WU YiMin; CHEN Sheng (Jixie qiangdu)
Aiming at the problem of fatigue life prediction of 2A70 aluminum alloy in the full life range, carried out the tensile test of 2A70 aluminum alloy material, low-cycle fatigue test and high-cycle fatigue test under uniaxial tension and compression conditions. Discussed the advantages of life prediction by strain over the full life range. Proposed the strain fatigue full life curve model, and established the strain fatigue full life curve of 2A70 aluminum alloy. Calibrated the parameters of this model and three commonly used models through the test results, compared and analyzed the prediction results of four models. The results show that the life prediction results of the new model proposed in this paper are all within the range of triple error band, the average error and dispersion are small, and the life prediction accuracy is better than the other three models. The new model is more suitable for the fatigue life prediction of 2A70 material under the same strain ratio.